Can an occupational therapy intervention increase independence in activities of daily living (ADL) in people who use homecare re-ablement services? - Whitehead, Phillip J. (2016)
Homecare re-ablement services have been widely implemented by local authorities in England, although there are widespread variations in relation to occupational therapy input within them. These services aim to improve users’ ability to manage independently at home and reduce the need for other health and social care services. It is not known whether outcomes are better for people who receive occupational therapy as part of their homecare re-ablement compared with those who do not. This thesis reports a programme of work investigating this, encompassing: a systematic review, a qualitative interview study, and a feasibility randomised controlled trial (RCT) of an occupational therapy intervention targeted at activities of daily living (ADL).